Involvement Of Mitochondria In Diclofenac – And Ibuprofen- Induced Hepatotoxicity - Moorthy, Mohanambal (2008)
Diclofenac and ibuprofen are commonly used non-steroidal anti-inflammatory drugs (NSAIDs) in the treatment of rheumatic diseases. However, these drugs are known to cause hepatotoxicity in patients. Recent in vitro studies indicated that the hepatotoxic effects of these NSAIDs are related to their ability to induce apoptosis by targeting the mitochondria. This study was carried out to investigate and to compare possible liver perturbation following diclofenac and ibuprofen administration to rats. Male Sprague-Dawley rats (n=144) were treated with 3mg/kg, 5mg/kg and 1Omg/kg diclofenac and ibuprofen in normal saline, intraperitonealJy at 500~I/rat/day for 15 days. The control group was administered with saline in a similar manner. Four rats from each group were euthanised every 3 consecutive days. While 200mg/kg diclofenac and ibuprofen-treated rats (n=4) were euthanised following a single dose 10 hours post-treatment. Upon euthanisation, the livers were removed and cleaned with normal saline. A section across the right lobe was taken and fixed in 10% (v/v %) formal saline and 4% (v/v) glutaraldehyde for light (H&E staining and TUNEL assay) and transmission electron microscopy, respectively. The remaining samples were kept under -80°C for Western blotting analysis. The three mg/kg diclofenac administered group at day 15 showed significant presence of microvesicles and lymphocytic infiltration. The five mg/kg diclofenac-treated rats revealed significant presence of microvesicles, lymphocytic and neutrophilic infiltrations at day 15. Liver sections obtained from rats administered with 10 mg/kg diclofenac showed significant presence of microvesic1es, mild lymphocytic and neutrophilic infiltration and inflammation. The five mg/kg and 10mg/kg ibuprofeninjected rats showed significant presence of microvesicles and mild focal lymphocytic and neutrophilic infiltrations. These observations were mainly seen around central veins (CVs). In TUNEL assay, 5mg/kg and IOmg/kg diclofenac and IOmg/kg ibuprofen administered rats, showed apoptotic cells around the CVs at day 15. Ultrastructural study revealed swollen and ruptured mitochondrial membranes in rats treated with 5mg/kg diclofenac, 10mg/kg diclofenac and 10mg/kg ibuprofen on day 15. Western blotting analysis showed constant expression of cytochrome c in liver homogenate and mitochondrial fraction on day 3,6,9, 12 and 15. However no cytochrome c expression was detected in the cytosolic fraction. In 200 mg/kg diclofenac and ibuprofen-treated rats, cytochrome c was detected in all 3 fractions; homogenate, mitochondrial and cytosol. The expression of cytochrome c is higher density in the cytosol from rats administered with diclofenac when compared to the expression in cytosol from rats treated with ibuprofen. It can be concluded that diclofenac is probably more potent in inducing changes in mitochondrial membrane leading to apoptosis. However, at therapeutic dosage both drugs did not induce prominent alteration in the mitochondria and the hepatocytes in general.